Effect of (LECA) as a Partial Replacement of Coarse Aggregate on Some Properties of Glass Fiber Reinforced Self-Compacting Concrete - Hiba Hassan Ghanem; Hadeel Khaled Awad (Journal of Engineering)
This study investigates fresh and hardened self-compacting concrete properties. LECA will be used in place of coarse aggregate in (0, 20, 40, and 60) % proportions in a partial replacement. First, four SCC mixes were made based on LECA volume fraction and then the second group was made by adding 1% glass fiber by volume to group one's mixes. Hardened concrete after 7, 28, and 56 days was tested for density, water absorption, and (compressive, splitting tensile, and flexural) strengths. Results suggest that LECA increases workability. Rising LECA percentage decreases compressive strength; for 60% LECA, the decrease was (51.90, 45.34, and 41.26) % for 7, 28, and 56 days, respectively. With 60% LECA replacement, flexural strength decreased by (54.38, 33.80, and 32.78) % for 7, 28, and 56 days, respectively. Density drops significantly with LECA, reaching its lower density at (60) % of LECA. Water absorption rises with the increase of LECA. After adding glass fiber workability dropped significantly, and hardened characteristics improved. Compressive strength increased slightly compared to the same mixtures without glass fibers. At20% of LECA the compressive strength increased by (5.58%) at 28 days compared to (60%) LECA at which the compressive strength increased by (3.82%). Glass fiber addition increased flexural strength significantly compared to the same mixes without glass fibers. The mixture with (20%) LECA had the greatest increase (24.46%) in 28 days, compared to the mix with (60%) LECA (18.22%). Density increased slightly with glass fibers. Glass fibers increase water absorption compared to the same mixes without glass fiber.